Development and validation of a rapid test system for detection of pork meat and collagen residues. (November 2016) - Masiri, J.; Benoit, L.; Barrios-Lopez, B.; Thienes, C.; Meshgi, M.; Agapov, A.; Dobritsa, A.; Nadala, C.; Samadpour, M.
Abstract: Mislabeling, contamination, and economic adulteration of meat products with undeclared pork tissues are illegal under regulations promulgated by numerous regulatory agencies. Nonetheless, analysis of the European meat industry has revealed pervasive meat adulteration, necessitating more extensive application of meat authentication testing. As existing methods for meat speciation require specialized equipment and/or training, we developed a detection system based on a lateral flow device (LFD) assay format capable of rapidly ( 35 min) identifying porcine residues derived from raw meat, cooked meat, and gelatin down to 0.01%, 1.0%, and 2.5% contamination, respectively. Specificity analysis revealed no cross-reactivity with meat derived from chicken, turkey, horse, beef, lamb, or goat. Comparison with a commercial ELISA kit and PCR method revealed similar if not improved sensitivity, with the added feature that the LFD-based system required considerably less time to perform. Accordingly, this test system should aid the food industry and food control authorities in monitoring for adulteration with pork. Highlights: Mislabeling, contamination and adulteration of meat products with pork are illegal. A detection based on LFD capable of rapidly identifying pork residues is developed. LOD for raw pork, cooked pork, and gelatin is 0.01%, 1.0%, and 2.5%, respectively. The LFD-based system requires considerably less time to perform than ELISA and PCR. The test system should aid food industry in monitoring for adulteration with pork.